2011
DOI: 10.1134/s181971241104012x
|View full text |Cite
|
Sign up to set email alerts
|

A morphological-histochemical study of neurodegenerative and regenerative processes in flexor and extensor collaterals of the sciatic nerve after crushing in the presence of PRP-1

Abstract: A comparative morphological and histochemical study of the dynamics of de and regenerative processes in the damaged sciatic nerve (SN) area was conducted in rats at different time points after crushing in the presence of proline rich peptide (PRP 1). We measured the activity of Ca 2+ dependent acid phos phatase (AP). At the fifth day after SN crushing on the site of injury, we observed changes in the directions of nerve fibers and disruption of their structure, in particular, swelling of Schwann hollow tubes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…It is shown that depressor post-stimulus manifestations in the form TD and PTD mediate GABA or glycine monoamines. Us shows the protective purpose of GABA in studies of nonspecific neurodegeneration, especially in the Deiters' nucleus (following unilateral labyrinthectomy) [51], in the spinal cord after lateral hemisection [53][54][55][56] on peripheral nerve injury [57][58][59][60][61], on amyloid model of AD [50,62,63] and also on the rotenone model of PD [64,65]; in neurons mainly the GABAergic nature, in which early involving depressor reactions are accompanied by the recovery process until its completion. Confirmation the assumption of the universal protective assignment of GABA-ergic inhibition is the fact that in some systems during development of the nervous system GABA promotes proliferation, migration, differentiation and maturation of the synapse, expression of the GABA(A) receptor [66].…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that depressor post-stimulus manifestations in the form TD and PTD mediate GABA or glycine monoamines. Us shows the protective purpose of GABA in studies of nonspecific neurodegeneration, especially in the Deiters' nucleus (following unilateral labyrinthectomy) [51], in the spinal cord after lateral hemisection [53][54][55][56] on peripheral nerve injury [57][58][59][60][61], on amyloid model of AD [50,62,63] and also on the rotenone model of PD [64,65]; in neurons mainly the GABAergic nature, in which early involving depressor reactions are accompanied by the recovery process until its completion. Confirmation the assumption of the universal protective assignment of GABA-ergic inhibition is the fact that in some systems during development of the nervous system GABA promotes proliferation, migration, differentiation and maturation of the synapse, expression of the GABA(A) receptor [66].…”
Section: Resultsmentioning
confidence: 99%